2015
DOI: 10.1007/s00122-015-2631-9
|View full text |Cite
|
Sign up to set email alerts
|

TaXA21-A1 on chromosome 5AL is associated with resistance to multiple pests in wheat

Abstract: A quantitative trait locus QYr.osu-5A on the long arm of chromosome 5A in bread wheat (Triticum aestivum L., 2n = 6x = 42; AABBDD) was previously reported to confer consistent resistance in adult plants to predominant stripe rust races, but the gene causing the quantitative trait locus (QTL) is not known. Single-nucleotide polymorphism (SNP) markers were used to saturate the QTL region. Comparative and syntenic regions between wheat and rice (Oryza sativa) were applied to identify candidate genes for QYr.osu-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…when initially released, however within a few years races of P. triticina with virulence to Lr17a increased rapidly and the resistance in Jagger was much less effective ( Long et al 1998 ). Jagger is currently still used extensively as a parent due to the presence of many elite resistance genes for abiotic and biotic stresses, and many current hard red winter wheat cultivars in the U.S. have Jagger in their pedigrees ( Fang et al 2011 ; Liu et al 2015 , 2016 ; Turner et al 2016 ).…”
mentioning
confidence: 99%
“…when initially released, however within a few years races of P. triticina with virulence to Lr17a increased rapidly and the resistance in Jagger was much less effective ( Long et al 1998 ). Jagger is currently still used extensively as a parent due to the presence of many elite resistance genes for abiotic and biotic stresses, and many current hard red winter wheat cultivars in the U.S. have Jagger in their pedigrees ( Fang et al 2011 ; Liu et al 2015 , 2016 ; Turner et al 2016 ).…”
mentioning
confidence: 99%
“…Further phylogenetic analysis using this subclade, along with putative homologs in 24 additional grass species, found that Rps8 LRR-RK and Xa21 are orthologs ( Figure 6b; Supplemental Tables 5 and 6 ). Extensive phylogenetic and functional characterization has been performed on the putative orthologs of Xa21 in the grasses (Tan et al, 2011; Cantu et al, 2013; Yang et al, 2013; Liu et al, 2016; Wang et al, 2019). In agreement with previous phylogenetic analysis, the wheat RK Xa21-like1 (TaXa21L1), Xa21-like2 (TaXa21L2), and Xa21-like3 (TaXa21L3) correspond to TraesCS4D01G352700.1, TraesCS2D01G585500.1, and TraesCS5A01G285000.1 (RefSeq2.0) (Cantu et al, 2013), and group distinct from the Xa21 subclade.…”
Section: Resultsmentioning
confidence: 99%
“…TaXA21‐A1 , a wheat orthologue of the OsXA21 ‐like gene on chromosome 9 in rice ( Oryza sativa L.), was identified as a candidate gene for QYr.osu‐5A (Liu et al., 2016). Located on chromosome 5AL, QYr.osu‐5A was originally associated with adult‐plant resistance to stripe rust in the recombinant inbred line population Jagger/2174, with secondary effects on powdery mildew and Hessian fly biotype GP reaction (Fang et al., 2011; Liu et al., 2016). Gallagher and Iba have the same TaXA21‐A1 allele as Duster, and like Duster, Iba contains Lr34 – Yr18 – Sr57 , but Gallagher does not.…”
Section: Characteristicsmentioning
confidence: 99%
“…Stripe rust resistance in Duster is conferred by the pleiotropic adult-plant resistance gene Lr34-Yr18-Sr57 and QYr.osu-5A. TaXA21-A1, a wheat orthologue of the OsXA21-like gene on chromosome 9 in rice (Oryza sativa L.), was identified as a candidate gene for QYr.osu-5A (Liu et al, 2016). Located on chromosome 5AL, QYr.osu-5A was originally associated with adult-plant resistance to stripe rust in the recombinant inbred line population Jagger/2174, with secondary effects on powdery mildew and Hessian fly biotype GP reaction (Fang et al, 2011;Liu et al, 2016).…”
Section: Disease Insect and Acid-soil Reactionsmentioning
confidence: 99%